(untitled) (Revista Iberoamericana de Bioética, 2021)
The biomedical applications of neuroscience are divided into those that use evaluative techniques and those that use interventional methods. Given the bio-psycho-social reach of these technologies, a philosophical and bioethical debate seems inevitable. Thus, from the philosophy of the mind, two main areas of reflection appear: conceptual problems on reading, control and mental transference, and the ontological difficulties related to the identity of the "Homo cyborg". Conversely, applied bioethics has been interested in two fundamental issues: the difference between treatment and neuronal enhancement, and the application of classical bioethical principles to neuroenhancement. Thus, applied neuroethics is proposed as a normative area from which to evaluate the use of neurotechnology.